2018
DOI: 10.1177/1077801218802640
|View full text |Cite
|
Sign up to set email alerts
|

“If He’s Abusing You . . . the Baby Is Going to Be Affected”: HIV-Positive Pregnant Women’s Experiences of Intimate Partner Violence

Abstract: Pregnancy represents a time of increased risk for intimate partner violence (IPV), and an HIV diagnosis further increases the vulnerability of this at risk group. This study explores experiences of recent IPV using qualitative interviews with N=12 HIV-positive pregnant women recruited from a clinical setting in South Africa, a location with high global prevalence of IPV and HIV. Partner dynamics around IPV resulted in HIV shame and stigma, and adversely affected engagement in HIV care and HIV treatment behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…For example, the mothers in this study experienced feelings of failure, guilt, and inadequacy in not being able to protect their children. This is consistent with previous South African research that has found that experiences of IPV can undermine a woman’s confidence in her ability to adequately care for and protect her children from harm [ 35 ]. The societal notions of the ‘good mother’ which were founded upon idealized versions of motherhood may especially create additional tension for women who mother within the context of IPV [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…For example, the mothers in this study experienced feelings of failure, guilt, and inadequacy in not being able to protect their children. This is consistent with previous South African research that has found that experiences of IPV can undermine a woman’s confidence in her ability to adequately care for and protect her children from harm [ 35 ]. The societal notions of the ‘good mother’ which were founded upon idealized versions of motherhood may especially create additional tension for women who mother within the context of IPV [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…In one qualitative study, Marais et al (2019) interviewed 12 HIV-positive pregnant women asking questions about their experiences of IPV during their current pregnancy and the impact of the violence on their mental, physical, and sexual health. The respondents described a wide range of experiences including physical, emotional, and sexual abuse.…”
Section: Resultsmentioning
confidence: 99%
“…The six qualitative studies were conducted in South Africa (Marais et al, 2019), Kenya (Colombini et al, 2016; Onu et al, 2017), Swaziland (Colombini et al, 2016; Mulrenan et al, 2015), Malawi (Chilemba et al, 2014), and Uganda (Emusu et al, 2009). Participants were mostly HIV-positive women aged 18 and older sampled from various health-care centers.…”
Section: Resultsmentioning
confidence: 99%
“…Even if IPV or HIV are not disclosed, internalised stigma can still impact a person’s ability to seek help, therefore jeopardising opportunities for diagnosis and management [ 38 , 39 ], or worsening their mental health [ 38 , 65 , 66 ]. The presence of both HIV and IPV stigma in this review have been described to leave expectant and current mothers feeling isolated [ 67 , 68 ], creating a barrier to both HIV-related and pregnancy-related care [ 68 ]. A crucial step in IPV management, after these services have been made available, is recognising the need for them.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by previous qualitative research [ 40 ]. IPV and fear of IPV can result in women not feeling confident enough to request condom use [ 57 ], placing them at increased risk of HIV and other STIs [ 40 , 68 , 70 ]. Furthermore, Hampanda [ 50 ] demonstrates how IPV can reduce PMTCT medication adherence.…”
Section: Discussionmentioning
confidence: 99%